Design research : synergies from interdisciplinary perspectives - Simonsen, Jesper (Routledge, 2010)
Design Research is a new interdisciplinary research area with a social science orientation at its heart, and this book explores how scientific knowledge can be put into practice in ways that are at once ethical, creative, helpful, and extraordinary in their results. In order to clarify the common aspects - in terms of features and approaches - that characterize all strands of research disciplines addressing design, Design Research undertakes an in-depth exploration of the social processes involved in doing design, as well as analyses of the contexts for design use. The book further elicits `synergies from interdisciplinary perspectives' by discussing and elaborating on differing academic perspectives, theoretical backgrounds, and design concept definitions, and evaluating their unique contribution to a general core of design research. This book is an exciting contribution to this little explored field, and offers a truly interdisciplinary approach to the treatment of design and the design process. It is valuable reading for students in disciplines such as design studies and theory, participatory design, informatics, arts based education, planning, sociology, and interdisciplinary programmes in humanities and technology.